Gastric myeloid sarcoma - A report of two cases addressing diagnostic issues - Viijaya Gadage; Gargi Zutshi; Santosh Menon; Tanuja Shet; Sudeep Gupta (Indian Journal of Pathology and Microbiology, 2011)
Presented herein are two cases of gastric myeloid sarcoma to highlight the diagnostic conundrum and pointers toward accurate diagnosis in such instances. The first case was a 35-year-old man with an ulceronodular mass in the body of stomach. Multiple biopsies were reported as inconclusive chiefly due to the fact that the lamina propria infiltrate was innocuous and failed to mark with CD20 or CD3. Subsequently the patient had extensive disseminated disease which was recognized as myeloid sarcoma but patient succumbed to the disease soon. The second case was a 25-year-old boy who presented with symptoms of gastric outlet obstruction since 6 months. An endoscopy revealed diffuse gastric wall thickening which on biopsy was recognized as myeloid sarcoma but patient developed intestinal obstruction and required ileal resection for symptomatic relief, postoperative patient never recovered and succumbed to the disease. Both patients had marrow involvement by acute myeloid leukemia (AML-M2) with a normal leukocyte count in peripheral blood. Thus gastric myeloid sarcomas are prone to a delayed diagnosis chiefly due to rarity. Pathologist should think of myeloid sarcoma in a hematolymphoid appearing tumor in stomach that is CD20, CD3 negative, has avid Ki67 and shows an infiltrate chiefly centered in lamina propria.